INDICATORS AND CALCULATION PARAMETERS IN THE ASSESSMENT OF ECOSYSTEM SERVICES FOR BIODIVERSITY CONSERVATION - KOROHODA, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2024)
Background. The concept of ecosystem services (ES) is closely related to the concept of biodiversity conservation. Urban green spaces (UGS) are areas of importance for urban biodiversity conservation. UGSs can effectively provide biodiversity services if they form an ecological network. The issue of assessing ecosystem services for biodiversity conservation in cities, where the assessment of ES is based on the "ecological network" approach, is currently not sufficiently covered. The development of a set of assessment indicators, calculation parameters, and a methodology for assessing ecosystem services for biodiversity conservation in the city has become the goal of this work.Methods. In this paper, we have developed an assessment methodology based on determining the effectiveness of the UGSs performance of "eco-network" functions. Differences in the indicators of biodiversity conservation are caused by a number of factors. The natural factors include the presence of rare and endangered species within the UGS; landscape diversity; metric and qualitative characteristics of green spaces. Anthropogenic factors include the degree of landscape transformation.Results. Accordingly, these factors have become indicators for assessing: biopopulation, landscape diversity, nature conservation, territorial, phase-anthropisation and phase-ethological sustainability. The calculated parameters are: biopopulation potential indicator, integral indicator of landscape diversity, indicator of conservation status, sufficient dimensionality, phase- anthropisation sustainability index, etc. These parameters make it possible to implement the assessment methodology at two territorial levels (citywide and local) and determine the effectiveness of the urban blue-green infrastructure (BGI) or a particular UGS in performing the biodiversity conservation function. The effectiveness of UGS s is determined depending on their condition. At the city-wide level, the effectiveness is determined through the interconnectedness of the elements of the GIS.Conclusions. Effectiveness indicators, based on the Harrington's desirability function, allow to establish the scope of biodiversity conservation ES. The assessment based on this methodology can be a useful tool in urban planning decision-making, as it allows identifying green spaces that require priority action to create conditions for biodiversity conservation.
Keywords: Urban green spaces; ecosystem services; biodiversity conservation